Study of the role of functional variants of SLC22A4, RUNX1 and SUMO4 in systemic lupus erythematosus. Issue 6 (25th October 2005) - Orozco, G; Sánchez, E; Gómez, L M; González-Gay, M A; López-Nevot, M A; Torres, B; Ortego-Centeno, N; Jiménez-Alonso, J; de Ramón, E; Sánchez Román, J; Anaya, J M; Sturfelt, G; et al.
Abstract : Background: Functional polymorphisms of the solute carrier family 22, member 4 ( SLC22A4 ), runt related transcription factor 1 ( RUNX1 ) and small ubiquitin-like modifier 4 ( SUMO4 ) genes have been shown to be associated with several autoimmune diseases. Objective: To test the possible role of these variants in susceptibility to or severity of systemic lupus erythematosus (SLE), on the basis that common genetic bases are shared by autoimmune disorders. Methods: 597 SLE patients and 987 healthy controls of white Spanish origin were studied. Two additional cohorts of 228 SLE patients from Sweden and 122 SLE patients from Colombia were included. A case–control association study was carried out with six single nucleotide polymorphisms (SNP) spanning the SLC22A4 gene, one SNP in RUNX1 gene, and one additional SNP in SUM04 gene. Results: No significant differences were observed between SLE patients and healthy controls when comparing the distribution of the genotypes or alleles of any of the SLC22A4, RUNX1, or SUMO4 polymorphisms tested. Significant differences were found in the distribution of the SUMO4 genotypes and alleles among SLE patients with and without nephritis, but after multiple testing correction, the significance of the association was lost. The association of SUMO4 with nephritis could not be verified in two independent SLE cohorts from Sweden and Colombia. Conclusions: These results suggest that the SLC22A4, RUNX1, and SUMO4 polymorphisms analysed do not play a role in the susceptibility to or severity of SLE.